African-American women college and university presidents: their role, experiences, challenges and barriers - Woodard, Sophia J., author; Davies, Timothy, advisor (Colorado State University. Libraries, 2009)
The purpose of this study was to examine four phenomena: role, experiences, challenges, and barriers of African-American women college and university presidents with a particular focus on the role based on the social conscious concept of "race upliftment" as espoused by Dr. W.E.B. DuBois and other African American scholars of the early 20th century. The review of literature suggests that there is a tendency to advocate for race upliftment primarily when leading an African-American institution or an Historically Black College and University (HBCU). As a qualitative phenomenological study, in-depth personal and telephone one to two hour interviews were conducted with eight African-America women college and university presidents of two and four-year institutions. Each interview was tape-recorded with the full permission of the president. A demographic questionnaire was completed by each president prior to conducting the interview. All eight recorded tapes were transcribed and the data analysis process involved six major steps based on Creswell (1994). The qualitative software HyperRESEARCH was used to assist in analyzing and coding the data, and in compiling the qualitative report. Reading and memoing were used for code and theme development, and a reflexive journal, member checking, clarifying research bias and peer review were used for validity and trustworthiness. The findings of this study revealed that role plays a significant component for these women and is categorized into several areas that include: (1) nurturer and protector of students; (2) fiscal manager; (3) values and skills practitioner; (4) spiritual practitioner and servant; and (5) communications expert. Their work in role directly impacts and influences how they view and serve in their role as leaders. In fact, these African-American women college and university presidents developed many of their concepts of role based on the multi-faceted experiences they encountered both on their journey to the presidency and in this journey. Many of their experiences encompassed their formative years of education and training/rearing in their homes and communities, the educational journeys they traveled through college and graduate school, as well as the varied professional encounters in academia prior to becoming presidents. The collective energy of these experiences were an exciting and foundational part of their leadership development and journeys to the presidency which were also consumed with challenges and barriers. These challenges and barriers were centered around five specific areas that comprised the challenges of leadership: (1) addressing and resolving fiscal insolvency; (2) personal challenges such as parenting roles and living apart from family members(children and husbands); (3) managing health and wellness; (4) gender, race and age disparity; and (5) professional challenges such as status quo issues, college-wide communication issues, dealing with alumni concerns and problems with overbearing board-of-trustee members. In essence, the role, experiences, challenges and barriers that emerged from the data (voices) of these African-American women college and university presidents comprise the journey they traveled in becoming and being president.
Covers not scanned.
Keywords: African American college presidents; Women college presidents